Immunization Strategies To Block the Herpes Simplex Virus Type 1 Immunoglobulin G Fc Receptor - Lin, Xiaoqing (American Society for Microbiology, 2004)
Herpes simplex virus type 1 (HSV-1) glycoprotein gE functions as an immunoglobulin G (IgG) Fc receptor (FcγR) that promotes immune evasion. When an IgG antibody binds by the F(ab′)(2) domain to an HSV antigen, the Fc domain of some of the same antibody molecules binds to the FcγR, which blocks Fc-mediated functions. gE is a type 1 membrane glycoprotein with a large ectodomain that is expressed on the virion envelope and infected-cell surface. Our goal was to determine if immunizing with gE protein fragments could produce antibodies that bind by the F(ab′)(2) domain to gE and block the FcγR, as measured by competitively inhibiting nonimmune human IgG binding to the FcγR. Three gE peptides were constructed in baculovirus spanning almost the entire ectodomain and used to immunize mice and rabbits. Two fragments were highly effective at producing antibodies that bind by the F(ab′)(2) domain and block the FcγR. The most potent of these two antibodies was far more effective at blocking the FcγR than antibodies that are only capable of binding by the Fc domains to the FcγR, including anti-gC, anti-gD, and nonimmune IgG. These results suggest that immunizing with gE fragments has potential for preventing immune evasion by blocking activities mediated by the HSV-1 FcγR.